Research and the ambiguity of reflexivity and ethical practice. - Hastings, Wendy (Discourse: Studies in the Cultural Politics of Education, 2010)
This paper examines the methodological dilemmas associated with analytical framing as an aspect of the research process. Doing qualitative research potentially changes a researcher - changes their sense of self, who they think they are, who they want to become. The paper examines the ethical dilemma of what that change might mean - for the project, the researcher and the participants. Would respondents be so open if they were that aware the research(er) potentially could change during the performance of the research project? What are the implications, if any, of engaging respondents with the intention of telling their story as a narrative inquiry, then analysing the data through a feminist post-structuralist lens? How does a researcher honour the perspectives of the participants, while simultaneously bringing to bear the critique and understanding provided by employing a post-structuralist lens? The paper pays particular attention to the interactive interview, as it generated possibilities for a researcher to establish a level of trust and rapport such that (emotional) stories could be heard and then later, represented as interpretations of the researcher.